Early Language Literacy and Numeracy (ELLN) and the National Achievement Test (NAT) Performance of Learners in MIMAROPA - Pacia, Francis L. (International Journal of Arts, Sciences and Education, 2024)
This study aims to determine the contribution of the ELLN program to the academic performance of learners in the MIMAROPA region, as measured by the National Achievement Test (NAT) scores. Specifically, it seeks to ascertain the extent of this contribution. Quantitative data was collected through questionnaires and historical records, complemented by qualitative insights from focused-group discussions. Thematic and statistical analyses were employed to examine the data. The study revealed significant improvements in learners’ skills across the seven school divisions in the MIMAROPA region, particularly in language literacy and numeracy. Despite variations in implementation effectiveness, the ELLN program consistently fostered skills development among learners, indicating its positive impact on academic achievement. Moreover, the ELLN program has contributed positively to the academic performance o learners in the MIMAROPA region. However, ongoing efforts are needed to address challenges and ensure sustained program effectiveness. This research offers valuable insights for policymakers and educators to enhance early c